Naïve and capricious: Stumbling into the ring of self-control conflict - Kristian Ove R. Myrseth; Conny Wollbrant (European School of Management and Technology (ESMT), 2011)
We model self-control conflict as a stochastic struggle of an agent against a visceral influence, which impels the agent to act sub-optimally. The agent holds costly pre-commitment technology to avoid the conflict altogether and may decide whether to procure pre-commitment or to confront the visceral influence. We examine naïve expectations for the strength of the visceral influence; underestimating the visceral influence may lead the agent to exaggerate the expected utility of resisting temptation, and so mistakenly forego pre-commitment. Our analysis reveals conditions under which higher willpower and lower visceral influence reduces welfare. We further demonstrate that lowering risk aversion could reduce welfare. The aforementioned results call into question certain policy measures aimed at helping people improve their own behavior.
urn:nbn:de:101:1-201201176351
Keywords: D01; D03; D69; D90; 650; self-control; temptation; inter-temporal choice; pre-commitment; Persönlichkeitspsychologie; Selbstevaluation; Theorie